MEDIA BIAS: ANALISIS WACANA KRITIS PEMBERITAAN ISU POLITIK DI INDONESIA MEDIA VICE.COM/ID - Mohammad Iqbal Ali Maghrobi (Arkhais - Jurnal Ilmu Bahasa dan Sastra Indonesia, 2021)
Information that so massively will be one form of media role. The communication process must be there until keingkun and become the object of literacy. Good authority from the readings in interpreting every message that is by the media. Media bias exists to know which is the main topic. This curious study of word selection and koala lexicon became the main focus of the topic of analysis. This research is a qualitative descriptive initiative that midwives to describe the findings using analysis of Critical Discourse Analysis (CDA), descriptive qualitative analysis of news reports in Vice.com/id in the political rubric edition of march to April 2020 and then it will be carried out further in the collection of data and sample results, as well as analysis tools. In this study, the data analyzed both qualitatively descriptive findings related to linguistic aspects of word selection and lexical location ko, the goal was to know, where, and found that vice.com/id media became biased political issues in Indonesia during the research period. The results of this study Vice.com/id to ence to political issues in Indonesia with the good name of the neutral party in this case. The findings are based on the results of an analysis of diction election data by the vice.com/id media and the rah kea rah traktual audience to critically critical what is related to social issues around. Next, the findings are the result of analysis data, there are three conclusions that can be in-picture, namely Idonesian kopat consists of leletakksikal ko (nouns, verbs, adjectives).